Capital Structure and International Debt Shifting - Laeven, Luc (IMF Working Papers; Working Paper ;, 2007)
This paper presents a model of a multinational firm's optimal debt policy that incorporates international taxation factors. The model yields the prediction that a multinational firm's indebtedness in a country depends on a weighted average of national tax rates and differences between national and foreign tax rates. These differences matter because multinationals have an incentive to shift debt to high-tax countries. The predictions of the model are tested using a novel firm-level dataset for European multinationals and their subsidiaries, combined with newly collected data on the international tax treatment of dividend and interest streams. Our empirical results show that corporate debt policy indeed not only reflects domestic corporate tax rates but also differences in international tax systems. These findings contribute to our understanding of how corporate debt policy is set in an international context.